An Overview of the Development Electronic Wallet in Encouraging Economic Growth in the Indonesian Territory - Andres Dharma Nurhalim (Primanomics : Jurnal Ekonomi & Bisnis, 2020)
This article aims to discuss the problem of a electronic wallet capable of driving economic growth in the territory of Indonesia for businesses and the public. The analytical method used in conducting this research is to use one literature with another literature as a basis for arguing. With the development of digital wallet, it is hoped that it can accelerate economic growth and financial inclusion in Indonesia towards Indonesia with the inclusion of digital technology and is also expected to be able to reduce geographical barriers that can later be eliminated with digital capabilities. So that everyone can easily transaction through an electronic wallet.